EFFECT OF FEEDING OAK (Quercus aegilops) ACORNS ON MILK PRODUCTION, MILK COMPOSITION AND SOME BLOOD BIOCHEMICAL PARAMETERS OF BLACK GOATS - Hidayet, Hoger M.; Mustafa, Kamal N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Twenty four Black goat does at 1st week post kidding were adapted to control diet for 2 weeks and then blocked into 4 groups (6 does/group) to be fed on one of the experimental diets (0, 5, 10 and 15% oak acorns) to study the effect of different levels of oak acorns on milk yield, milk composition and some serum biochemical traits. Results revealed that at 10th week of lactation, there was a significant increase in daily milk yield in does fed on 15% oak acorns. In contrast the group fed on 15% oak acorns exhibited a significant decrease in milk protein and solid non-fat contents at 10th week of lactation. The milk lactose yield was significantly higher in group fed on 15% oak acorns at 10th week of lactation. The serum glucose concentration at 8th week of lactation was significantly higher in does fed on 10% oak acorns while at 10th week; it was significantly higher in does fed 5% oak acorns. It could be concluded that feeding does on diets containing 15% oak acorns caused a significant increase in daily milk yield of Black goats and a significant decrease in milk protein content.